Analisis Perbandingan Tarif Eksisting dan Tarif Ideal Berdasarkan Biaya Operasional Kendaraan (BOK) dan Break Even Point (BEP) - Fitriana, Fitriana; Purnama, Jaka (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Determining the ideal vehicle rental service rate is crucial for maintaining the sustainability and profitability of a transportation business. This study aims to compare the existing rates with the ideal rates based on the calculation of Vehicle Operating Costs (BOK) and Break Even Point (BEP) analysis. The method used is a quantitative approach with a case study on a fleet of chemical tanker trucks. The analysis results show that the current existing rates are lower than the ideal rates calculated based on BOK plus a profit margin. The case study demonstrates that by using the ideal rates, the company can reach the break-even point (BEP) faster. In this study, the S-H200 fleet with an ideal rate of IDR 3,192,540 reaches BEP at 147 trips per year compared to the rate of IDR 2,800,000 requiring 177 trips per year. Similarly, the U-H202 fleet reaches BEP at 143 trips per year with a rate of IDR 3,461,929, compared to 199 trips per year with the rate of IDR 2,800,000. This means that using the ideal rates accelerates the recovery of the fleet investment costs.